Continuous Practice Quality Improvement Initiative for Communication of Critical Findings in Neuroradiology. (September 2015) - Babiarz, Lukasz S.; Lewin, Jonathan S.; Yousem, David M.
The authors examined faculty's compliance with a hospital-approved neuroradiology critical findings (CFs) policy, which requires urgent verbal communication with the clinical team when 17 specific critical pathologies are identified. During June 2011 to July 2013, 50 random neuroradiology reports were sampled monthly for the presence of CFs and appropriate action. Faculty were provided ongoing feedback, and at the end of 2 years, the medical records for cases with noncommunicated CFs were reviewed to identify potential adverse outcomes. Of the 1200 reviewed reports, 195 (16.3%) had and 1005 (83.8%) did not have a CF. A total of 176 of 195 (90.3%) cases with CFs were communicated, and compliance increased from 77.4% to 85.6% ( P = .027) since the monthly sampling was instituted; 1 of 19 (5.3%) noncommunicated CFs resulted in a potential adverse event. The ongoing monthly feedback resulted in improved faculty compliance with the CF policy. However, a small number of cases with CFs are still not being communicated.